PENERAPAN AKUNTANSI WAKAF DI PROVINSI BANTEN - Safira Hijriah; M. Reza Hidayatullah; Salsabillah, Salsabillah; Mukhlishotul Jannah (Cahaya Ilmu Bangsa, 2024)
This research examines the application of waqf accounting in waqf management institutions in Banten Province with a focus on the implementation of PSAK 112, the accounting standard for waqf in Indonesia. This research was conducted at the Regional Office of the Ministry of Religious Affairs of Banten Province as one of the centers of waqf information and supervision in the area. The purpose of this study is to understand how waqf institutions record and report waqf assets and benefits in accordance with the standard, evaluate the obstacles faced in its implementation, and examine the role of local government in supporting more transparent and accountable waqf management. This research uses qualitative methods through interviews and document analysis as primary and secondary data sources. The results are expected to provide a clearer picture of waqf accounting practices in Banten Province as well as recommendations to improve professionalism and public trust in waqf management in this area.